Sub-chronic oral toxicity screening of quercetin in mice - Patrice Cunningham; Emma Patton; Brandon N. VanderVeen; Christian Unger; Ahmed Aladhami; Reilly T. Enos; Sarah Madero; Ioulia Chatzistamou; Daping Fan; E. Angela Murphy; Kandy T. Velázquez (BMC, 2022)
Abstract Background Quercetin is an organic flavonoid present in several fruits and vegetables. The anti-inflammatory, antiviral, antioxidant, cardio-protective, anti-carcinogenic and neuroprotective properties demonstrated by this dietary supplement endorses it as a possible treatment for inflammatory diseases and cancer. Unfortunately, conflicting research has cast uncertainties on the toxicity of quercetin. The main purpose of this study was to determine if quercetin has any toxic properties in mice at doses that have shown efficacy in pre-clinical studies regarding cancer, cancer therapy, and their off-target effects. Methods A sub-chronic toxicity study of quercetin was examined in male and female CD2F1 mice. Three different doses of quercetin (62, 125, and 250 mg/kg of diet) were infused into the AIN-76A purified diet and administered to mice ad libitum for 98 days. Body weight (BW), food consumption, water intake, body composition, blood count, behavior, and metabolic phenotype were assessed at various timepoints during the course of the experiment. Tissue and organs were evaluated for gross pathological changes and plasma was used to measure alkaline phosphatase (AP), aspartate transaminase (AST), and alanine transaminase (ALT). Results We found that low (62 mg/kg of diet), medium (125 mg/kg of diet), and high (250 mg/kg of diet) quercetin feeding had no discernible effect on body composition, organ function, behavior or metabolism. Conclusions In summary, our study establishes that quercetin is safe for use in both female and male CD2F1 mice when given at ~ 12.5, 25, or 50 mg/kg of BW daily doses for 14 weeks (i.e. 98 days). Further studies will need to be conducted to determine any potential toxicity of quercetin following chronic ingestion.